2010
DOI: 10.1074/jbc.c110.176990
|View full text |Cite
|
Sign up to set email alerts
|

The First Type III Repeat in Fibronectin Activates an Inflammatory Pathway in Dermal Fibroblasts

Abstract: Remodeling of the fibronectin matrix occurs during a variety of pathological and regenerative processes. Cellular generated tensional forces can alter the secondary and tertiary structure of the fibronectin matrix and regulate the exposure of cryptic activities that directly impact cell behavior. In the present study,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
53
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 31 publications
(28 reference statements)
4
53
0
Order By: Relevance
“…It was shown that exposure of fibroblasts to FNIII1c, a stable unfolded intermediate of FNIII1, can elicit TLR4-dependent inflammatory signaling and induce cytokine synthesis. 41,42 This region of the fibronectin molecule is exposed through tensional forces within the rigid fibrotic microenvironment. These observations have clear implications for fibrosis, since fibrotic tissue is characterized by increased stiffness and mechanical forces.…”
Section: The Alternately-spliced Fibronectin Isoform Acts As An Endogmentioning
confidence: 99%
“…It was shown that exposure of fibroblasts to FNIII1c, a stable unfolded intermediate of FNIII1, can elicit TLR4-dependent inflammatory signaling and induce cytokine synthesis. 41,42 This region of the fibronectin molecule is exposed through tensional forces within the rigid fibrotic microenvironment. These observations have clear implications for fibrosis, since fibrotic tissue is characterized by increased stiffness and mechanical forces.…”
Section: The Alternately-spliced Fibronectin Isoform Acts As An Endogmentioning
confidence: 99%
“…50 Thus, in addition to integrins, Fn-fs, as an endogenous ligand of Toll-like receptors 2 and 4, could act through its engagement, given that both receptors are present in SF. 48,51 Moreover, both stimuli induce the activation of MAPK signaling, implicated in the activation of Runx2 and other transcription factors, such as the NF-kB, 13e15,46,52 which also induce the expression of Wnt. 53,54 Therefore, we can hypothesize that IL-1b and 45-kDa Fn-fs induce aggrecanases expression by activation of the transcription factor Runx2, mainly through the ERK-MAPK signaling.…”
Section: Q18mentioning
confidence: 99%
“…9,[14][15][16][17] Upon adsorption to solid surfaces, the conformation of Fn at the interface appears to depend largely on the characteristics of the surface. Fn has been seen to adopt an extended conformations on hydrophilic surfaces and compact, globular conformations on hydrophobic surfaces 18,19 Furthermore, other factors such as surface chemistry and topography have been found to play an important role.…”
Section: Introductionmentioning
confidence: 99%